Communication Campaigns That Combine Fun and Learning - Misbah Khan (Research Journal of Psychology, 2024)
Within the ongoing history of storytelling, one component that has persisted for a very long time is the idea of combining pleasure and wisdom in equal measure. Throughout the course of human history, different nations have utilised a variety of cultural expressions, such as music, theatre, dance, and other folk media, for extended periods of time as a way of instructing their citizens, effecting social transformation, and engaging in recreational activities. The idea of "entertainment-education" is a relatively recent phenomenon that has acquired significance in recent decades due to intentional incorporation in various forms of media such as popular music, radio, television, comic comics, and other forms of media (Singhal & Rogers, 1999; Valente, Kim, Lettenmaier, Glass, & Dibh 1994). This intentional incorporation has contributed to the growth of the phenomenon known as "entertainment-education."Miguel Sabido, a Mexican television writer, producer, and director, was inspired to create a framework for including both entertaining and educational elements in soap operas as a result of the success that Simplemente Marfa had among its audience as well as the unintentional educational impact that the show had. Sabido drew his inspiration from both the show's success among its audience as well as its impact. Between the years 1975 and 1982, Sabido produced seven different series of television soap operas that were aimed at educating viewers while still being entertaining. According to Nariman (1993), these activities were crucial in fostering the adoption of family planning methods, increasing participation in adult literacy programmes, and furthering gender equality. The entertainment-education soap operas that were created by Sabido were able to attract audiences that were comparable to those that other soap operas on Televisa were able to attract, which contributed to the financial success of Televisa, the most important television network in Mexico. Keywords: Communication Campaigns, Combine Fun and Learning.